Response of fertility and agro-chemical on growth and yield of different varieties of clusterbean - Yogi, Rekha; Sharma, O.P.; Verma, H.P.; Kanwar, Krishna; Shivran, A.C. (Annals of Agricultural Research, 2016)
A field experiment was conducted during kharif season of 2013 to study response of clusterbean varieties to fertility levels and agro-chemicals at SKN College of Agriculture, Jobner. The experiment consisted of two varieties (RGC-1038 and RGC-1066), three treatments of fertility levels (control, 50% RDF and 100% RDF) and three treatments of agro-chemicals (control, thiourea 500 ppm twice at vegetative and pre flowering stage and thiourea 100 ppm twice at vegetative and pre flowering stage) thereby making eighteen treatment combinations tested in randomized block design with three replications. The results indicated that RGC 1066 variety recorded significantly higher plant height 60 DAS and at harvest and dry matter per meter row length at 30 DAS, 60 DAS and at harvest, number of pods/plant and seeds/pod, test weight, seed, stover and biological yield as compared to variety of RGC-1038. The result further indicated that application of 100% RDF significantly gave higher plant height at 60 DAS and at harvest similarly, dry matter per meter row length at 30 DAS, 60 DAS and at harvest, number of pods/plant and seeds/pod, test weight, seed, stover and biological yield recorded higher over control and 50% RDF. Likewise, application of agro-chemical @ thiourea (500 ppm) significantly increased the plant height at 60 DAS and at harvest and dry matter per meter row length at 30 DAS, 60 DAS and at harvest, number of pods/plant and seeds/pod, weight, seed, stover yield and biological yield and remained at par with the application of agro-chemical @ TGA (100 ppm) over control. However, plant height at 30 DAS remained materially unchanged under different varieties, fertility levels and agro-chemicals.